Development of Science Modules Based on a Culturally Responsive Teaching Approach on Banten's Typical Pottery Crafts to Scientific Literacy - Dinda Wulandari Hermina Putri; Siti Romlah Noerhodijah; Ratu Bai Rohimah; Trian Pamungkas Alamsyah (UNIVERSITAS NEGERI MEDAN, 2026)
This study was conducted based on field observations showing a lack of fundamental science literacy skills and limited teaching materials to support them. Therefore, a science module based on a culturally responsive teaching (CRT) approach was developed utilizing Banten's traditional pottery craft to facilitate the scientific literacy of seventh-grade students. This study aimed to analyze the validity of the CRT-based science module for improving scientific literacy. The research and development (R&D) method was employed using the ADDIE development model, which was limited to three stages: analysis, design, and development. Data were collected through validation questionnaires using instruments for expert validation. Nine validators, comprising subject matter experts, teaching material experts, and practitioner experts, conducted the validation. The obtained data were analyzed using quantitative and qualitative methods. The results showed that the science module was classified as